2015
DOI: 10.1161/atvbaha.114.303215
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and Noncanonical Vascular Endothelial Growth Factor Pathways

Abstract: The last five years have witnessed a significant expansion in our understanding of VEGF signaling. In particular, the process of canonical activation of VEGFR tyrosine kinases by homodimeric VEGF molecules have now been broadened by the realization that heterodimeric ligands and receptors are also active participants in the signaling process. While heterodimer receptors were described two decades ago, their impact, along with the effect of additional cell surface partners and novel autocrine VEGF signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 79 publications
3
35
1
Order By: Relevance
“…Previously, Loh and Choong () demonstrated the enhancement of cell migration on porous 3D scaffolds. The involvement of cell–cell contact (involving the release of soluble factors) and cell–scaffold interaction (specifically binding to the cell receptors or presented by noncanonical signalling action; Domigan, Ziyad, & Iruela‐Arispe, ) could contribute to abovementioned behaviour. Thus, as presented in Figure e,f, the penetrated cells could be the HDF and the cells on the surface could be HEK.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Loh and Choong () demonstrated the enhancement of cell migration on porous 3D scaffolds. The involvement of cell–cell contact (involving the release of soluble factors) and cell–scaffold interaction (specifically binding to the cell receptors or presented by noncanonical signalling action; Domigan, Ziyad, & Iruela‐Arispe, ) could contribute to abovementioned behaviour. Thus, as presented in Figure e,f, the penetrated cells could be the HDF and the cells on the surface could be HEK.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that VEGFR2 signals cells in an ‘autocrine’ or ‘intracrine’ fashion, leading to increased receptor activity within the cytosolic (endosome) and/or nuclear compartments [3336]. Endothelial cells can also release exosomes containing sequestered molecules that then modulate neighbouring cells [3739].…”
Section: Discussionmentioning
confidence: 99%
“…miR‐342‐5p could inhibit EC proliferation through 2 mechanisms. One is that miR‐342‐5p attenuated VEGF‐induced Akt phosporylation, which is a major signal transduction event downstream from VEGFR2 during angiogenesis 6, 7. Moreover, Wei et al reported that miR‐342‐5p directly targets Akt1 through its 3′ UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) receptors, a class of receptor tyrosine kinases, regulate vascular permeability and endothelial proliferation, migration, survival, and differentiation 6. VEGFA is the major ligand for VEGFR and binds to VEGFR2 to trigger receptor dimerization and autophosphorylation at several tyrosine residues, which in turn activate the downstream phospholipase C‐γ–protein kinase pathway, leading to activation of the c‐Raf, MEK, and mitogen‐activated protein kinase cascade and the phosphoinositide 3‐kinase and Akt pathway 6, 7. Notch signaling is an evolutionarily highly conserved pathway mediating contact‐dependent signaling between neighboring cells 8.…”
Section: Introductionmentioning
confidence: 99%